Innovative model for Assessing Human Assets - Sasirekha, A. (Journal of Contemporary Research in Management (JCRM), 2013)
There is an old adage that â€œyou canâ€™t improve it if you canâ€™t measure itâ€. Until recently, the value of an organization is measured through the traditional balance sheet, e.g., Building, Plant, Materials, Money, etc. It was viewed as a sufficient reflection of the organizationâ€™s assets. However,Â  with the growing emergence of the knowledge economy, the traditional valuation has been put into question due to the non-inclusion of the Human capital in its purview as it is an important part of an organizationâ€™sÂ  total value. The value of Human Resource in an organization should be measured / valued for the sustainable growth of the organization. Hence, the concept of measuring human resources has emerged in the recent past and a few experts have developed methods for the same. A detailedÂ  study has been made and proposed a new formula for measuring the value of human resources. By using the proposed formula, the total value of Human Assets in an organization can be valued and may be used forÂ  taking measures to increase the Human resource asset.